2011
DOI: 10.1051/0004-6361/201015204
|View full text |Cite
|
Sign up to set email alerts
|

A pan-chromatic view of the galaxy cluster XMMU J1230.3+1339 atz= 0.975

Abstract: Context. Observations of the formation and evolution of massive galaxy clusters and their matter components provide crucial constraints on cosmic structure formation, the thermal history of the intracluster medium (ICM), galaxy evolution, transformation processes, and gravitational and hydrodynamic interaction physics of the subcomponents. Aims. We characterize the global multi-wavelength properties of the X-ray selected galaxy cluster XMMU J1230.3+1339 at z = 0.975, a new system discovered within the XMM-Newt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 106 publications
(115 reference statements)
1
36
0
Order By: Relevance
“…Consistently, the X-ray selected cluster RDCS J0910+5422, exhibits a red sequence although its early-type galaxy population appears to be still forming (Mei et al 2006a;Tanaka et al 2008). With a total mass of about 10 14 M ), RDCS J0910+5422 is as massive as XMMU J0338.7+0030 and four times less massive than XMMU J1230.3+1339 at z = 0.975 (Fassbender et al 2011a;Lerchster et al 2010).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Consistently, the X-ray selected cluster RDCS J0910+5422, exhibits a red sequence although its early-type galaxy population appears to be still forming (Mei et al 2006a;Tanaka et al 2008). With a total mass of about 10 14 M ), RDCS J0910+5422 is as massive as XMMU J0338.7+0030 and four times less massive than XMMU J1230.3+1339 at z = 0.975 (Fassbender et al 2011a;Lerchster et al 2010).…”
Section: Discussionmentioning
confidence: 84%
“…Secondly, it fosters the investigation of the evolution of the galaxy population, the baryon mass component of groups/clusters, the thermodynamics and chemical abundance of the ICM (e.g., Postman et al 2005;Mei et al 2006a,b;Balestra et al 2007;Gobat et al 2008;Maughan et al 2008;Giodini et al 2009;Mantz et al 2010b;Santos et al 2010;Strazzullo et al 2010). About twenty clusters at z = 0.8−2.1 have been discovered and studied in some detail (e.g., Stanford et al 2001Stanford et al , 2002Stanford et al , 2006Blakeslee et al 2003;Mullis et al 2005;Demarco et al 2007;Hilton et al 2007Hilton et al , 2009Eisenhardt et al 2008;Lamer et al 2008;Menci et al 2008;Wilson et al 2009;Kurk et al 2009;Tanaka et al 2010;Papovich et al 2010;Henry et al 2010;Gobat et al 2011;Fassbender et al 2011a). However, a better sampling in redshift and total mass is necessary to build a representative sample of high-z groups and clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demarco et al 2007;Fassbender et al 2011;Muzzin et al 2012;Andreon et al 2014;Stanford et al 2014). Comparable work on more common, lower-mass haloes at z > 0.3 -the progenitors of today's massive clusters -is more difficult and hence more limited, but several studies have shown that group galaxies indeed evolve differently from the field, at least for z < 0.8 (e.g.…”
mentioning
confidence: 99%
“…With total clean exposure time of 20 min, it is a valuable complement to the Calar Alto imaging data. For the reduction of the pre-imaging data we followed the same procedure as Schwope et al (2010) and Fassbender et al (2011a).…”
Section: Xmmu J03022-0001mentioning
confidence: 99%